Konstruksi Instrumen Penilaian Baca Tulis Quran (BTQ) Di IAIN Pekalongan - Ma'mun Ma'mun (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2020)
This study aims to develop a valid BTQ matriculation assessment instrument based on the indicators of the BTQ assessment program at IAIN Pekalongan. This type of research is research development with a quantitative descriptive approach. The floating stage includes the preparation of test specifications, expert validation, trials, and product implementation. Data collection techniques and instruments through observation and questionnaires are presented in the form of test items to analyze the suitability of competency standards in each component. The results of this study indicate that 16 items representing BTQ assessment instrument indicators meet valid criteria with the results of the validity of 4 aspects (tajwid, fashohah, gharib, adab) the greatest factor load of 1.05 on the accuracy indicator of reading the law of Imalah and isymam, while the lowest is 0.81 at indicator of reading the Qur'an by closing the genitals. The results of the BTQ instrument construction analysis meet 8 of 9 index criteria of goodness of fit so that it can be used in measuring the ability to read the Qur'an